Analisis Kemampuan Berpikir Kritis Siswa SMA dalam Memecahkan Masalah Matematika Ditinjau Dari Gender - Risala, Rahmatul; Yohanie, Dian Devita; Darsono (Polinomial : Jurnal Pendidikan Matematika, 2025)
Critical thinking skills should be developed and taught in every subject, especially mathematics to help students make better decisions and understand the world. Gender differences can also affect the way individuals deal with problems critically. This study aims to describe the critical thinking skills of male and female students in solving problems in statistics material using critical thinking indicators according to facione. This study uses a descriptive research method with a qualitative approach involving one male and one female student in grade 10 of SMA Negeri 3 Kediri, who were selected based on student learning outcomes. This data analysis technique includes data reduction, data presentation and drawing conclusions. The results of the study showed differences between male and female students in problem-solving strategies. Although both understand the problems given, male students tend to be able to explain verbally by telling the problem and its solution in their own language. While female students show a more detailed, structured and careful approach in writing. Both of these styles are effective in achieving the correct solution, although with different characteristics at each stage of the problem-solving process